Big data analytics and knowledge discovery : 17th International Conference, DaWaK 2015, Valencia, Spain, September 1-4, 2015, Proceedings /: 17th International Conference, DaWaK 2015, Valencia, Spain, September 1-4, 2015, Proceedings. (2015) - Unknown
No abstract available